Unlocking the dehalogenation potential of lead oxide (PbO) via its co-pyrolysis with polyvinyl chloride (PVC) and novel brominated flame retardants (NBFRs) - Mohamed Shafi Kuttiyathil; Labeeb Ali; Mirza Belal Beg; Wey Yang Teoh; Mohammednoor Altarawneh (Case Studies in Chemical and Environmental Engineering)
The Stockholm Convention treaty of the United Nations Environment Program has impeded the mass production of legacy brominated fire retardants (BFRs) paving the route to introduce novel BFRs (NBFRs) into the industrial market. Tetrabromobisphenol A diallyl ether (TBBPA-DAE), is a widely emerging NBFR with a high rate of production. The deleterious impacts, neurobehavioral consequences and toxic effects of NBFRs have been well-documented. Co-pyrolysis of BFRs with metal oxides has emerged as a potential de-bromination technique in e-waste recycling that curtails the bromine release into the environment. Herein, a multitude of characterization studies are done to probe into the debromination efficiency of lead oxide (PbO) during its co-pyrolysis with TBBPA-DAE via products (char, gas and condensates) analyses. The thermogravimetric analysis suggested a pyrolytic run up to 600 °C. The GCMS analysis showed that the release of brominated compounds was completely restricted in the condensate at 600 °C by increasing the phenol production. This was due to the capture of HBr by the PbO to form PbBr2, which was validated by the spectral, XRD and SEM-EDX analyses. The IC analysis also endorsed a better efficiency of PbO in HBr capture (80.04 %) in comparison to the HCl capture (45.57 %) proving that PbO is a good debromination agent envisaging further probes to other emerging NBFRs. The study also investigates the de-chlorination of PVC to establish the universal de-halogenation capacity of PbO toward mixed halogenated plastic wastes.